Investigations on Zinc Isotope Fractionation in Breast Cancer Tissue Using in vitro Cell Culture Uptake-Efflux Experiments - Schilling, Kathrin; Harris, Adrian L.; Halliday, Alex N.; Schofield, Christopher J.; Sheldon, Helen; Haider, Syed; Larner, Fiona (Frontiers in Medicine, 2022)
Zinc (Zn) accumulates in breast cancer tumors compared to adjacent healthy tissue. Clinical samples display isotopic compositions (delta-66Zn) of Zn in breast cancer tissue that are light relative to healthy samples. The underlying mechanisms causing such effects are unknown. To investigate if the isotopic discrimination observed for in vivo breast cancer tissue samples can be reproduced in vitro, we report isotopic data for Zn uptake-efflux experiments using a human breast cancer cell line. We used the MDA-MB-231 cell line as a model for triple receptor negative breast cancer. We determined Zn isotope fractionation for Zn cell uptake (delta-66Znuptake) and cell efflux (delta-66Znefflux) using a drip-flow reactor to enable comparison with the in vivo environment. The MDA-MB-231 cell line analyses show Zn isotopic fractionations in an opposite direction to those determined with in vivo breast cancer tissue samples. Uptake of isotopically heavy Zn (delta-66Znuptake = +0.23 ± 0.05‰) is consistent with transport via Zn transporters (ZIPs), which have histidine-binding sites. Zn excreted during efflux is isotopically lighter than Zn taken up by the cells (delta-66Znefflux = -0.35 ± 0.06‰). The difference in Zn isotope fractionation observed between in vitro MDA-MB-231 cell line experiments and in vivo breast tissue samples might be due to differences in Zn transporter levels or intercellular Zn storage (endoplasmic reticulum and/or Zn specific vesicles); stromal cells, such as fibroblasts and immune cells may also contribute. Although, additional experiments using other human breast cancer cell lines (e.g., MCF-7, BT-20) with varying Zn protein characteristics are required, the results highlight differences between in vitro and in vivo Zn isotope fractionation.